Ciało fortepianu – artykulacja doświadczenia cielesnego w korespondencji Fryderyka Chopina - Świtka, Aleksandra (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article focuses on the presentation and analysis of selected excerpts from Frédéric Chopin’s letters from the 1824-1849 period that illustrate their author’s attitude towards physical experiences. In contrast to the “disembodied” reception of the artist that reproduces the “soul of the piano” metaphor, the article describes a broad representation of the composer’s texts on physical appearance, the role of the body in the performance act, living through illness and the oncoming death. The cross-sectional and chronologically ordered study presented in the article shows the evolution of the subject’s attitude towards his own body along the progress of his illness. It is at the same time an illustration of the style and imagery used by the author of the letters while describing specific aspects of physical experience.